Research-Based Teacher Education and Professional Development. Achievements and Contributions of EDiTE - Rozalia Małgorzata Ligus (University of Lower Silesia, 2013)
This article's aim is to describe some of the sources of the European debate over the third cycle studies in teacher education in Europe. Then it will introduce the international Project EDiTE as one of the collaborative initiatives concerning the European scientific proposal of the teachers' lifelong learning development. Next, some good practices of promoting the doctoral research based teacher education on national levels will be presented. Finally, in the article, there will be revealed selected findings of the EDiTE team that are focused on the current needs in teacher education that have been pointed by different stakeholders of five European countries represented by the project consortium, while interviewing them in 2013 y. The main goal of this article is to involve the stakeholders in a thought provoking debate for future roles of teachers in Europe, but not through looking for a 'standardized teacher model' or to create a 'European super teacher', but to see the dilemmas that should be shared while questioning 'What makes a teacher European?,' as Michael Schratz underlines, in a diversity of national identities and in the face of challenges of 21st century.